2000
DOI: 10.1007/s001470050691
|View full text |Cite
|
Sign up to set email alerts
|

Heparin and phentolamine combined, rather than heparin alone, improves hepatic microvascular procurement in a non-heart-beating donor rat-model

Abstract: Improvement of organ procurement from non-heart-beating donors (NHBDs) could increase the donor organ pool for liver transplantation. Whether anti-coagulative and anti-vasospastic substances can improve hepatic microvascular preservation from NHBDs is unknown. In donor rats which were pretreated with either heparin (n = 6) or heparin combined with phentolamine ( n = 7) 10 min prior to cardiac arrest, the extent and homogeneity of hepatic microvascular reperfusion was assessed at the end of a 60-min period of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
(8 reference statements)
0
3
0
1
Order By: Relevance
“…Optimizing cardiovascular physiology is also critical (59). When donor hemoglobin concentration is reduced, whole blood or packed red cells are transfused and, if there is potential for thrombophilia as in DCD donation, systemic heparinization is administered to maintain and improve graft perfusion (60). Heparinization may also have immunological advantages by decreasing anti‐TNFα activity, monocyte and T‐cell infiltration by reducing expression of graft major histocompatability complex II antigen (61).…”
Section: Donor Optimizationmentioning
confidence: 99%
“…Optimizing cardiovascular physiology is also critical (59). When donor hemoglobin concentration is reduced, whole blood or packed red cells are transfused and, if there is potential for thrombophilia as in DCD donation, systemic heparinization is administered to maintain and improve graft perfusion (60). Heparinization may also have immunological advantages by decreasing anti‐TNFα activity, monocyte and T‐cell infiltration by reducing expression of graft major histocompatability complex II antigen (61).…”
Section: Donor Optimizationmentioning
confidence: 99%
“…In livers, the induction of dual (i.e., hepatic arterial and portal venous) perfusion, as well as the increase of the portal venous perfusion pressure, markedly improve microvascular inflow of the preservation solution, which consequently reduces the overall heterogeneity of microcirculatory preservation quality (135,138). In addition, pretreatment of donors with heparin and phentolamine, as done clinically in organ harvesting from non-heart-beating donors, has shown that only combined application of heparin and phentolamine, but not heparin alone, improves microvascular procurement (136). However, a warm preflush of the organs of non-heart-beating donors containing streptokinase in RingerЈs lactate has been highly effective to almost normalize microvascular perfusion conditions of the preservation solution in both livers and kidneys (186,187).…”
Section: Techniques For the Study Of Microcirculatory Derangements Inmentioning
confidence: 99%
“…The organ shortage and rising number of critical patients for liver transplantation are associated with the allocation of marginal organs procured from critical brain‐dead donors 1–3. To attenuate posttransplant organ dysfunction, research efforts during the last decade not only have focused on novel therapeutic strategies to reduce preservation and reperfusion injury but also have included pretreatment regimens for these critical organ donors 4–6…”
mentioning
confidence: 99%